The Influence of Regulator Grow Essence Auksin IAA And The Onion Extract to Multiplication Cuttings Meranti Sabut (Shorea parvifolia Dyer.). - Muhammad Masli; Maya Preva Biantary; Heni Emawati (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2019)
The purpose of this research are to know hormone Auksin IAA response and onion extract to the ability live of shoot cuttings Shorea parvifolia Dyer.This research using by Completely Randomized Design pattern by 3 x 3 factors and every repetition contain 30 cuttings with the hormone treatment or regulator grow  essence auksin IAA (A) by 0,1 gr/ml close, onion extract (B) content by 100% and didn’t by treatment or control (O).The result of this research are : (1) the influence of regulator grow auksin IAA essence and the onion extract to multiplication cuttings meranti sabut (Shorea parvifolia Dyer.) that indicate using hormone auksin IAA is the best with 91,11% presentation live by onion extract have 87,78% while presentation live and did not by control have 85,56% live presentation. (2) the influence of regulator auksin IAA essence and extract onion to multiplication cuttings meranti sabut (Shorea parvifolia Dyer.) to the sum of root, the long of root, the sum of new leaf and the new shoot are different and not real.